Dynamical Systems Discontinuity, Stochasticity and Time-Delay - Luo, Albert C. J. (Springer New York : Imprint: Springer, 2010)
Dynamical Systems: Discontinuous, Stochasticity and Time-Delay provides an overview of the most recent developments in nonlinear dynamics, vibration and control. This book focuses on the most recent advances in all three areas, with particular emphasis on recent analytical, numerical and experimental research and its results. Real dynamical system problems, such as the behavior of suspension systems of railways, nonlinear vibration and applied control in coal manufacturing, along with the multifractal spectrum of LAN traffic, are discussed at length, giving the reader a sense of real-world instances where these theories are applied. This volume also: Discusses discontinuous dynamical systems as applied to real-world issues, like the behavior of suspension systems in railways, the multifractal spectrum of LAN traffic and their correlations, as well as the effect of nonlinear vibration and applied control on coal manufacturing. Includes material on time-delay systems as they relate to linear switching systems, dynamics of complex networks and machine tools with multiple boundaries. Presents numerous theories and aspects of vibration and control, using worked mathematical examples and empirical evidence to argue the pros and cons of all theories. Dynamical Systems: Discontinuous, Stochasticity and Time-Delay is the ideal book for engineers and academic researchers working in areas like mechanical and control engineering, as well as applied mathematics.